Bibliotheraphy: Layanan bimbingan konseling di perpustakaan - Dian Hasfera (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2018)
Biblioteraphy is one of the treatment in helping the client to overcome the trauma or their problems. Bibliotherapy is seen as a cost-effective treatment. Can be used in various social groups and age groups, as well as effective for healthy people who want to share useful literature for personal growth and development or character. Knowledge or personal experience of most clients is very limited about the problems they face, because the client only refers to the experience themselves. Bibliotherapy can provide useful feedback for clients to address these problems. Much information can be obtained through reading activities. Bibliotherapy makes one learn new facts, has different ways of looking at / approaching problems and has the ability to alternate in solving problems. As one of the information institutions that are rich in reference and reading sources, the library can be the location where the biblioteraphy is implemented. Exposure in this paper is the result of a study from various sources that discusses the basic concepts of bibliotherapy as a counseling guidance service implemented in the library. The results of this study are very useful for counselors, psychologists, librarians, and teachers who are interested in learning about how books can be used as a therapeutic tool for users / clients / learners who have psychological disorders.